Effects of membrane electrode assembly properties on two-phase transport and performance in proton exchange membrane electrolyzer cells. (10th January 2016) - Han, Bo; Mo, Jingke; Kang, Zhenye; Zhang, Feng-Yuan
Highlights: A MEA model for characterizing two-phase transport and performance in PEMECs is developed. The model has been validated with experimental data. LGDL properties have significant influences on the two-phase transport behaviors. Pore size has more significant effects on cell performance at high current densities. The limiting current density closely related to the LGDL properties. Abstract: A mathematical model is developed to simulate the two-phase transport behaviors and the performance in a proton exchange membrane electrolyzer cell (PEMEC). The parameter effects of the liquid/gas diffusion layer (LGDL), including contact angle, porosity, and pore size, on the capillary flow and liquid water distribution are comprehensively studied. In addition, the effects of the LGDL pore size and membrane humidity on the performance and efficiency of PEMEC are also investigated. The results indicate that LGDL properties have significant impacts on its capillary pressure and liquid water distribution, which consequently affects the two-phase transport and performance in the PEMEC. Increasing the porosity and/or pore size or decreasing the contact angle can enhance the liquid water saturation along the LGDL thickness direction, and consequently improve the performance and efficiency of PEMEC. The variation of PEM humidity contributes to a portion of the cell ohmic loss as well.